2022
DOI: 10.1016/j.ijid.2021.10.026
|View full text |Cite
|
Sign up to set email alerts
|

End-of-life use of antibiotics: a survey on how doctors decide

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…There have been studies on medical staff’s perceptions of antibiotic stewardship in EOL patients. One survey study found that many doctors who provide palliative care tend to initiate and maintain or extend antibiotics use in EOL patients, even in cases where antibiotics might not be appropriate or where the risks might outweigh the benefits [ 4 ]. Another study found that physicians have divergent attitudes toward the management of infectious diseases in terminally ill patients with cancer [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been studies on medical staff’s perceptions of antibiotic stewardship in EOL patients. One survey study found that many doctors who provide palliative care tend to initiate and maintain or extend antibiotics use in EOL patients, even in cases where antibiotics might not be appropriate or where the risks might outweigh the benefits [ 4 ]. Another study found that physicians have divergent attitudes toward the management of infectious diseases in terminally ill patients with cancer [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in physician’s perspective, decide not to initiate antibiotics is tough when clinicians suspect infection in end-of-life clinical conditions. 4 Not initiate antibiotics become challenging in some infections, such as urinary tract infections, that may be more likely to improve symptomatically with antimicrobial therapy compared to other infections. 5 Studies that suggest this tendence did not use the same method to evaluate symptomatic improve.…”
Section: Dear Editormentioning
confidence: 99%
“…A suspensão de antibióticos é uma das decisões que mais gera dúvidas na prática em CP. Um estudo 27 constatou que médicos atuantes em CP, apesar da formação na área, tendem a insistir em antibioticoterapia mesmo diante dos dias ou das horas finais, inclusive realizando substituição de medicamentos em caso de ausência de resposta. Em situações específicas, como diante de 11/15 pacientes oncológicos com baixa funcionalidade e com risco de evolução ao óbito, há maior cuidado e chances de suspensão da terapêutica em questão.…”
Section: /15unclassified